Evaluation of drought and salinity tolerance potentials of different soybean genotypes based upon physiological, biochemical, and genetic indicators - Alzahrani, Yahya (Frontiers in Plant Science, 2024)
The present study has evaluated different soybean genotypes for understanding the salt and drought tolerance mechanisms based on, physiological traits (photosynthesis, stomatal conductance, chlorophyll, cell membrane stability), antioxidant enzymes (superoxide dismutase, catalase, peroxidase), reactive oxygen species (H2O2, O2 •-), osmolytes (glycine betaine, proline, Na + /K + ), plant water relations (relative water content, water potential, solute potential) and related genes expression (GmCAT1, GmPOD1, GmSOD, GmP5CS, GmNHX1, GmAKT1, GmDREB1, GmARF1). The experiment was conducted in a two factorial arrangement using randomized complete block design (RCBD) with genotypes as one factor while salt, drought and control treatments as other factor. All physiological traits, relative water content and water potential decreased significantly in all soybean genotypes due to individual and combined treatments of drought and salt stress, with significantly less decrease in soybean genotypes G4620RX, DM45X61 and NARC-21. Besides, the activity of antioxidant enzymes, production of ROS, accumulation of osmolytes, solute potential and Na + /K + ratio were increased significantly in all soybean genotypes under salt and water deficit conditions. As a whole, the soybean genotypes G4620RX, DM45X61 and NARC-21 showed the maximum enzymatic activity with less increase in ROS and Na + /K + in addition to high accumulation of osmolytes and increase in solute potential. Correspondingly, the genotypes exhibiting high physiological and biochemical tolerance to drought and salt stresses showed the high expression of genes imparting the stress tolerance. Moreover, correlation, heatmap and principal component analysis further confirmed the varying physiological and biochemical responses of all soybean genotypes under individual and combined application of drought and salinity stresses. Overall, the present study confirmed that plants opt for the integrated physiological, biochemical and genetic approaches to counteract the harmful effects of environmental stresses.